Peran Mahasiswa dalam Mengimplementasikan Pendidikan Berbasis Masjid untuk Siswa MD Sabilul Ibaad Kabupaten Pamekasan - Moh. Abdullah Rosyidi; Ricky Ricky; Ferdianto Ferdianto; Qurrota A’yun; Yayik Indah Susnita; Risma Shinta Maduri; Danang Prastyo (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The implementation of community service carried out by KPM IAIN Madura students in improving the quality of understanding of Islam in Ponteh Village, Galis District, Pamekasan Regency is through Dirosa Islamiyah which is manifested through various Islamic education and teaching programs for Muslim women and children. The results of the Dirosa Islamiyah activities for Muslim women in Ponteh Village show that some Muslim women and children in Ponteh Village before joining the Dirosa Islamiyah program had little knowledge and understanding of Islam. However, after participating in Dirosa Islamiyah activities, Muslim women and children in Ponteh Village had an increase in their knowledge and understanding of Islam.